L’éducation de Nietzsche. Réactualisation des considérations sur l’honneur : une des valeurs de l’ethos universitaire - Olivier Marty (Recherches en Éducation)
Nietzsche is a philosopher of education who participates the European lifelong learning policy : based on Homeric contests, he gives a meaning within education to the value of honor – honor that we take as raw material for an exegesis of his youth works. We take Nietzsche as a learner more than an educator and we do with him a genealogy of honor as a moral value – this being an anthropological constant within our civilization. Honor appears as a scientific ethos around which gravitate all uni-versitarians. Reading how Nietzche learnt, educators and universities can learn how to use honors to grow. Honor appears as a monument to inspire great men. Heidegger will read this art as an aesthetic leading to learn how to overpass oneself.